A new Notacanthurus Tshernova, 1974 and a new Rhithrogena Eaton, 1881 (subgenus Tumungula Zhou & Peters, 2004) from Thailand (Heptageniidae, Ephemeroptera) - Braasch, Dietrich; Boonsoong, Boonsatien (Zootaxa, 2009)
Notacanthurus baei sp. n. (larva) and Rhithrogena (Tumungula) siamensis sp. n. (male, female and assumed larva) are described from northern Thailand. Diagnoses and line drawings of key characters are provided. Larvae of Southeast Asian Notacanthurus n.sp. resemble those of Palearctic Notacanthurus spp. in having a median ridge of spines directed posteriorly on terga, a similar patterning of terga with oblique stripes sloping inward, femoral cross bands and caudal filaments with whorls of small spines. Contrastingly, larvae of the new species bear claws with denticles, while the mature male larva exhibits prospective penis with distally paired portions of rounded lobes like those in most Electrogena Zurwerra and Tomka, 1984. Imagines of R. (T.) siamensis represent a second species of subgen. Tumungula Zhou and Peters, 2004. Males have balloon-shaped hypertrophied foreclaws, with first tarsal segment about 1.4x the length of the second, and divergent penis lobes without titillators. In contrast to R. (T.) unica the male styliger plate shows two sharp, inside directed projections, submedian lobes of the penis have circular gonopores lacking subapical spines.